Answer:
if you meant f(x) = (x - 1) /3 then f (g(x) ) = x
of if you meant f(x) = x - (1/3) then f(g (x)) = 3x + 2/3
Step-by-step explanation:
f(x) = x-1/3 and g(x) = 3x+1 what is (fog)(x)
f ( g(x) ) = (3x + 1) - (1/3) = 3x + 2/3
Or
if you meant f(x) = (x - 1) /3 then f (g(x) ) = x
of if you meant f(x) = x - (1/3) then f(g (x)) = 3x + 2/3
Answer:
it's option c x(7y)
Step-by-step explanation:
you don't need any order to multiply
Well, you want to find the value of x.
Answer:
2 11/12 or 35/12
Step-by-step explanation: